FREKUENSI PEMBERIAN PAKAN ARTEMIA TERHADAP KELANGSUNGAN HIDUP BENIH IKAN PATIN (Pangasius hypopthalmus) DI AKUARIUM - Jaya Admadi; Rini Marlida; Yulius Kisworo (Chlorophyl, 2021)
The study aims to determine the feeding frequency of Artemia on the survival rate of catfish fry (P. hypophthalmus). The fish used were catfish fry aged ten days after hatching. The number of fish in this study was 100 fish/aquarium in 9 aquarium. Completely randomized design was used as experimental design consisting of 3 treatment and 3 replicates. Treatment A with feeding 2 times a day, B with 4 times a day and C with 6 times a day. The result showed that the survival rate of catfish fry was found in treatment B (99,00%), followed by treatment C (98,33%). Meanwhile treatment A showed the lowest survival rate (90,33%). The result of the analysis of variance (ANOVA) showed that the calculated F value was 8,85 > F table 5% (5,14), which means that survival rate with different feeding frequency had a significant effect on the percentage of catfish fry survival. From the result of the BNJ test with the result of treatment B with treatment C there was no significance diferent but significantly different from treatment A, so it was found that the best survival rate was B treatment (feeding frequency 4 times a day). The result of water quality measured during this research showed that the temperature range 28,17 – 28,400C, pH range 7,9 – 8,2, DO 4,57 – 4,67 mg/l and NH3 range 0,02 – 0,03 mg/l. This situation shows that the range of temperature, pH, and DO can still be tolerated for the survival rate of catfish fry, as well as NH3